(untitled) - Steinberg, Roberta (New York, 2005)
Provides study tools for the computer-based Test of English as a Foreign Language (TOEFL), including diagnostic tests, skill reviews, practice questions, essay guidance, a complete transcript of the listening tests and exercises, test-taking strategies, screen captures, and two full-length practice tests with explained answers.
Keywords: Test of English as a Foreign Language,English language,Bài tập tiếng Anh,Tiếng Anh